Use of aviation by climate change researchers: Structural influences, personal attitudes, and information provision. (November 2020) - Whitmarsh, Lorraine; Capstick, Stuart; Moore, Isabelle; Köhler, Jana; Le Quéré, Corinne
Highlights: Large, international survey and experimental study of academic travel. Climate change researchers, especially professors, fly more than other researchers. Information provision increases intentions and policy support for reduced flying. Structural/social factors are stronger predictors of flying than attitudinal factors. Knowledge alone is insufficient to change workplace travel choices. Abstract: Aviation is a fast-growing sector, releasing more carbon dioxide per passenger kilometre than other transport modes. For climate change researchers, work-related travel – including for conferences and fieldwork – is a major carbon-emitting activity. At the same time, many argue that climate scientists have an important role in curbing their own aviation emissions to align their practices with their assertions in relation to emissions reduction. We examine the tensions between competing professional demands in relation to flying; measure levels of flying by climate and non-climate researchers; assess influences on choices and attitudes; and consider how information provision and structural changes might enable changes in practice. Study 1 entails a large, international survey of flying undertaken by climate change (including sustainability and environmental science) researchers and those from other disciplines (N = 1408). Study 2 tests effects of varying information provision on researchers' behavioural intentions and policy support to reduce flying (N = 362). Unexpectedly, we find climate change researchers – particularly professors – fly more than other researchers, but are also more likely to have taken steps to reduce or offset their flying. Providing information about the impacts of aviation increases behavioural intentions and support for institutional policies to reduce flying, particularly amongst more pro-environmental respondents. However, while attitudinal factors (e.g., personal norm) predict willingness to reduce flying, structural/social factors (e.g., family commitments, location) are more important in predicting actual flying behaviour. Recent initiatives to develop a low-carbon and more inclusive research culture within climate science and the broader research community thus need to be supported by broader policies and technologies to encourage and enable low-carbon and avoided travel.